2020
DOI: 10.1007/s10973-020-09709-5
|View full text |Cite
|
Sign up to set email alerts
|

Melt stabilization of polyethylene with natural antioxidants: comparison of a natural extract and its main component

Abstract: The efficiency of the natural extract, silymarin, was compared to its main component, silybin in the processing stabilization of polyethylene. The two compounds were applied as primary antioxidants in the concentration range of 0–500 ppm in combination with 1000 ppm Sandostab PEPQ phosphorous secondary stabilizer. The efficiency of the stabilizers was determined by the measurement of the concentration of unsaturated groups, the amount of residual PEPQ, melt flow rate (MFR), oxidation induction time and color o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Even hindered phenolic antioxidants discolor the polymer slightly, but the use of a phosphorous antioxidant sufficiently compensates for the effect. Natural antioxidants are either colored themselves [ 12,20,22,23 ] or their reaction products give the polymer a strong color. [ 21 ] The extract, as mentioned in the experimental part, has a slight yellowish color; thus, we might have expected only weak color in the product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even hindered phenolic antioxidants discolor the polymer slightly, but the use of a phosphorous antioxidant sufficiently compensates for the effect. Natural antioxidants are either colored themselves [ 12,20,22,23 ] or their reaction products give the polymer a strong color. [ 21 ] The extract, as mentioned in the experimental part, has a slight yellowish color; thus, we might have expected only weak color in the product.…”
Section: Resultsmentioning
confidence: 99%
“…The direct use of a natural extract for stabilization would be more advantageous, and a recent study showed that the natural extract of silymarin was a more efficient stabilizer than the main component of the extract, silybin. [23] Pomegranate (Punica granatum L.) is cultivated throughout the world in subtropical and tropical areas, mainly in Mediterranean and Asian countries and in several countries of North and South America. [24] Pomegranate is produced in large quantities in India, China, Iran, and Turkey; India is the main exporter of pomegranate in the world.…”
mentioning
confidence: 99%
“…However, the number of studies and, thus, scientific papers on the use of natural antioxidants for the stabilization of plastic products continuously increases. Flavonoids produced by plants, such as quercetin [ 15 , 16 , 17 ], rutin [ 18 ] and dihydromyricetin [ 19 ], proved efficient stabilizers in polyethylene, and the comparison of a natural extract, silymarin, to its main component, silybin, showed that extracts could be more efficient than purified single compounds [ 20 ]. Recently, pomegranate peel extract was used for the processing stabilization of polyethylene, and its efficiency exceeded that of the commercial hindered phenolic antioxidant, Irganox 1010 (I1010) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the different morphological aspects of components led to modifications in the compatibilization features ( Figure 9 ). The effects of inorganic materials, such as Hap [ 65 ], as well as polyphenol types of natural antioxidants [ 66 ], cause different thermal responses related to interface cohabitation, where crystalline islands are spread through amorphous material. The presence of Hap in the composites led to a decrease in Xc values compared with the LDPE/UHMWPE composites at all the irradiation doses.…”
Section: Resultsmentioning
confidence: 99%